Exploring the perceived knowledge of teacher educators and pre-service teachers on the differentiated instruction practices of teacher educators - Nketsia, William; Opoku, Maxwell P.; Amponteng, Michael; Mprah, Wisdom Kwadwo (Frontiers in Education, 2024)
Inclusive education involves creating effective learning environments that welcome and meet the diverse needs of all students. Differentiated instruction (DI) has been identified as a key instructional approach to addressing the diverse needs of all students in regular classrooms. While there is a large body of literature on DI, that relating to the non-Western context is sparse. Using comprehensive model of DI as a conceptual framework, this study examined teacher educators’ perceived usage of DI practices in teacher training institutions in Ghana. It used a questionnaire design based on the tenets of model for data collection. A total of 1,002 participants (199 teacher educators and 883 pre-service teachers) were recruited from four teacher training institutions in Ghana. The data were analyzed using confirmatory factor analysis, t-tests, and Hayes’s model for performing moderation analysis. The results show differences between pre-service teachers and teacher educators, with the former rating the latter lower on the perceived usage of DI. The study concludes with a discussion on the training needs of teacher educators in the usage of DI and enabling them to effectively model appropriate differentiated teaching experiences to beginning teachers.